The Coherent and Thermal Photons Radiation in the Enzyme - Gavahi, Mehrad (Revista de la Universidad del Zulia, 2020)
This paper presents the theoretical states of radiation field in the mechanism of enzyme, for state of thermal and coherent radiation by concept of the  quantum mechanics. For illustrating the energy and distribution of photon, we used simple concepts of the radiation field in the enzyme. We try to present the thermal radiation and coherent radiation happened in the biological microscopic system especially in the enzyme, and show that, these radiations could break the hydrogen bond pairs in the enzyme (substrate) at high temperature (above 323K) and show its effects on the relative activity of the enzyme.